The Effect Of Using Educational Media Flipbook For Adolescent Reproductive Health On Knowledge Of Sexuality In Students At The Faculty Of Mathematics And Natural Sciences, Bengkulu University - Novita, Rahma; Dewiani, Kurnia; Kurniati, Neng; Purnama, Yetti; Suriyati (Universitas STRADA Indonesia, 2024)
Background : Adolescence is a critical period in human development involving complex biological, psychological, and social changes. Method : The research employed a quasi-experimental method with a pre-post-test control group design. Conducted from August 2023 to March 2024, the study involved 86 respondents, divided into 43 intervention group participants and 43 control group participants. Result : The results showed a significant increase in sexual knowledge scores in the intervention group, from 65.12 to 80.41, while there was no substantial change in the control group. Conclution : The study concludes that the flipbook effectively enhances adolescents' sexual knowledge, as evidenced by a p-value < 0.05.